Characteristics of the material composition of atmospheric suspensions in Birobidzhan city - K. S. Golokhvast; I. L. Revutskaya; N. K. Khristoforova (Acta Biomedica Scientifica, 2013)
The article presents the results of research of nano- and microparticles of the atmospheric suspensions containing in snow of Birobidzhan in winter of 2011/2012 by means of scanning electronic microscopy with the power dispersive analysis. To exclude secondary pollution by anthropogenous aerosols tests (an atmospheric precipitation in the form of snow) were gathered during snowfalls. Only the top layer (5-10 cm) fresh-dropped out snow was collected. Snow was placed in the 3-liter sterile containers. The material analysis of suspensions was carried out on a light microscope Nikon SMZ1000 and scanning electronic microscope Hitachi S-3400N with power dispersive spectrometer Thermo Scientific. It was shown that in atmospheric suspensions of Birobidzhan particles of rocks, vegetable detrite and technogenic (black, slag and not-defined) educations prevail in decreasing order. Influence of combined heat and power plant and motor transportation outcomes on qualitative structure of atmospheric suspensions was revealed. In the typical sample taken around a railway crossing we defined (in decreasing order): not-defined technogenic particles, parts of rocks, plant detrite, metal microparticles (by results of the power dispersive analysis - mostly Fe). In a typical sample from the area of the ring highway we revealed (in decreasing order): not-defined technogenic particles, black spherules, plant detrite, parts of rocks (by results of the power dispersive analysis - mainly alyumosilicates), metal microparticles (by results of the power dispersive analysis - mostly Fe). In the typical sample taken around combined heat and power plant black spherules and not-defined technogenic particles were defined in major. In an inspection pure zone, despite removal from dusting sources, black and metallic (Fe, Ti, Co, W) particles are found. Among features of qualitative structure of tests in Birobidzhan city big specific weight of plant detrite in them, in comparison with other Far East cities, should be noted. The analysis of qualitative structure of atmospheric suspensions of Birobidzhan confirms its status as the cities with small population, one combined heat and thermoelectric power station (working on coal), moderate press of motor transport and an average as a whole level of atmospheric pollution.